A novel carboxy-dye reactive system of potential applicability to wool and nylon fibres. Part 1. Studies with model amines - Gomes, Jaime Rocha (1991)
Dyes containing carboxylic acid groups have the potential to be reacted with the amino groups of wool and nylon fibres by prior activation with ethyl chloroformate (forming a mixed anhydride). The scope of this reaction has been examined in solution using a range of carboxy dyes with cyclohexyl-amine or lysine as model amine substrates. The expected amides are formed in good yields, and have been isolated and characterised. A preliminary study of the reactive dyeing of wool andnylon-6.6 indicates that dyeings with high wet fastness can he achieved with this system.